2016
DOI: 10.1002/ange.201605400
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cyclo‐N5 in THF Solution

Abstract: Compelling evidence has been found for the formation and direct detection of the cyclopentazole anion (cyclo‐N5−) in solution. The anion was prepared from phenylpentazole in two steps: reduction by an alkali metal to form the phenylpentazole radical anion, followed by thermal dissociation to yield cyclo‐N5−. The reaction solution was analyzed by HPLC coupled with negative mode mass spectrometry. A signal with m/z 70 was eluted about 2.1 min after injection of the sample. Its identification as N5 was supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Pentazole N 5 H, a hydro-nitrogen molecule containing all-nitrogen aromatic ring N 5 , has been in the focus of intensive experimental efforts of synthetic chemists for at least a century [1][2][3][4] Although theory predicted its existence as a metastable species with a local minimum on the potential energy surface confined by a large activation barrier 5 , this planar pentagon of N atoms connected to one H atom is short-lived in the gas phase, making the synthesis of this last member of azole series very difficult [6][7][8] . After many unsuccessful attempts, the isolated but short-lived N − 5 anion has been produced in the gas phase 9,10 , followed by its recent observation in a THF solution 11 . However, synthesis of hydrogen-containing N 5 H still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Pentazole N 5 H, a hydro-nitrogen molecule containing all-nitrogen aromatic ring N 5 , has been in the focus of intensive experimental efforts of synthetic chemists for at least a century [1][2][3][4] Although theory predicted its existence as a metastable species with a local minimum on the potential energy surface confined by a large activation barrier 5 , this planar pentagon of N atoms connected to one H atom is short-lived in the gas phase, making the synthesis of this last member of azole series very difficult [6][7][8] . After many unsuccessful attempts, the isolated but short-lived N − 5 anion has been produced in the gas phase 9,10 , followed by its recent observation in a THF solution 11 . However, synthesis of hydrogen-containing N 5 H still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] The prime report published by Haas et al in 2016 has ended the race for detection of N 5 − in solution. [ 43 ] In their research, they showed the formation, separation and stability for N 5 – ion. The synthesis of pentazolate anion is carried out by the reduction of phenylpentazole using an alkali metal, which is followed by thermal dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of pentazolate anion is carried out by the reduction of phenylpentazole using an alkali metal, which is followed by thermal dissociation. [ 43 ] Countless experiments and efforts were made to figure out the structure, stability and properties of numerously diversified N‐ring structured compounds. [ 44–51 ] An attempt has also been made to probe the stability of N 5 H in water clusters.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of synthetic technology, more and more poly‐nitrogen species have been discovered and synthesized. [ 11–14 ] The most representative of them are three relatively stable ionic poly‐nitrogen species, N 3 − , N 5 + , and recently synthesized N 5 − . They can all exist in the form of salts that are stable at normal temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%